1983
DOI: 10.1007/bf00912089
|View full text |Cite
|
Sign up to set email alerts
|

Family adjustment, parental attitudes, and social desirability

Abstract: This study examines the role of social desirability response set on the report of marital adjustment, child adjustment, and parenting attitudes. Results from 69 married couples closely replicate previous self-report findings suggesting that the more positive the report of marital adjustment, the fewer the number of child problem behaviors endorsed by parents (r = -.19(69), p less than .05). When social desirability is controlled, however, the marital-child adjustment relationship is nonsignificant. Previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…A post hoc analysis indicated that parents scoring high on the social desirability scale reported significantly less reasoning, verbal aggressiveness, and violence tactics with their children than parents who scored low on the social desirability scale. This is an important and potentially confounding finding given the nature of this study (i.e., factors contributing to the types of tactics parents use when in a conflict situation with their children), and adds support to Robinson and Anderson's (1983) contention that social desirability response sets can influence self-reports on family dysfunction and adversely affect the data.…”
Section: Limitations Of the Studymentioning
confidence: 54%
See 1 more Smart Citation
“…A post hoc analysis indicated that parents scoring high on the social desirability scale reported significantly less reasoning, verbal aggressiveness, and violence tactics with their children than parents who scored low on the social desirability scale. This is an important and potentially confounding finding given the nature of this study (i.e., factors contributing to the types of tactics parents use when in a conflict situation with their children), and adds support to Robinson and Anderson's (1983) contention that social desirability response sets can influence self-reports on family dysfunction and adversely affect the data.…”
Section: Limitations Of the Studymentioning
confidence: 54%
“…Nedehof (1985) noted that social desirability was "one of the most common sources of bias affecting the validity of experimental and 18 JOURNAL OF SOCIAL SERVICE RESEARCH survey research findings" (p. 263). Social desirability reflects either the conscious (i.e., impression management) or unconscious (i.e., self-deception) distortion of responses to place the individual in a favorable light (Nederhof, 1985;Paulhus, 1984;Robinson & Anderson, 1983). This study safeguarded against the bias of social desirability by including a social desirability measure.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…These results were obtained despite the fact that no effort was made in constructing the DAS to control for the possible effects of conventionality and social desirability on responses. The DAS has been shown to have a significant, moderate correlation with social desirability [Robinson and Anderson, 1983], and parents of children with disability are reported to be prone to social desirability bias and denial [Walker et al, 1992]. However, professionals may misinterpret normative adjustment to a child's disability as denial [Robinson, 1993].…”
Section: Discussionmentioning
confidence: 96%
“…Test‐retest reliability for the Frequency and Problem scales were .86 and .88 respectively for a 3‐week period (Robinson et al, 1980). The ECBI has been shown to be independent of social desirability (Robinson & Anderson, 1983). Scores on the ECBI have also been shown to decline with psychological treatment (Eyberg & Ross, 1978; McNeil, Eyberg, Eisenstadt, et al, 1991).…”
Section: Methodsmentioning
confidence: 99%